Chemical and Drug Use in Dairy Farms of Hawassa Town, Southern Ethiopia - Haben Fesseha; Saliman Aliye; Temesgen Kifle; Mesfin Mathewos (Public Health, 2025)
AimThe current study was conducted to assess chemical and drug use in dairy farms of Hawassa town, Southern Ethiopia.Methods and MaterialsA total of 45 dairy farms were selected based on the willingness of the owner and the availability of information using a cross-sectional study from December 2017 to April 2018. Besides, data were collected through a questionnaire survey and close observation.ResultsAccordingly, based on observational assessment, most farms commonly used savlon (88.9%) iodine (60%) and detergent (20%) as antiseptics. Albendazole was the common anthelmintic by all dairy farms. Besides, Diazinon is used as acaricides (51.1%) and 57.8% of farms used sulfa drugs as an antiprotozoal agent. Similarly, all dairy farms in the study area used penicillin-streptomycin combination injection and ampicillin-cloxacillin combination for the treatment of mastitis. Based on a questionnaire assessment on 24 animal health assistants from different farms in of the study area, most (79.2%) did not remind owners to avoid the use or sale of animal products during withdrawal time. Out of the total, 27 (60%) of them offer or sell products to the public from animals treated with any of drugs without holding the withdrawal period of the drug.ConclusionThe current study revealed that there was a high risk of drug and chemical residues in dairy products in the study area which can be a great threat to public health. Consequently, awareness creation through mass education, training and extension service should be promoted in the study area in order to ensure better chemical and drug use and minimize its public health hazards.